Spatial and temporal ways of knowing sea level rise: Bringing together multiple perspectives. (7th March 2021) - McMichael, Celia; Kothari, Uma; McNamara, Karen E.; Arnall, Alex
Abstract: Sea level rise presents risks to ecosystems, populations, and infrastructure in low‐lying areas. This article considers diverse ways of knowing, understanding, and experiencing these risks. It explores differences and connections between knowledge produced through the technological methods of scientific research and that which emerges through the experiences and insights of local people. For example, while scientific assessments measure and forecast, among other things, the height and rate of vertical change in the sea level using instruments such as tide gauges and radar‐firing satellites, for local populations sea level rise is largely perceived and knowable through everyday processes and lived experiences of coastal changes as sea waters encroach onto the land. The review article reveals this diversity of knowledge and how it is produced. It considers how these different forms of knowledge might coalesce in ways that can more effectively inform understandings of, and responses to, the varied effects of sea level rise. Focusing specifically on spatial and temporal understandings of sea level rise—as the vertical rise of sea levels and inward encroachment of sea water, and timescales from the everyday to the decadal and centennial—this article concludes by arguing for the importance of integrating scientific measurement and modeling with local knowledge. It suggests that local and Indigenous knowledge should not merely represent an enrichment of scientific facts, but rather that bringing together local/Indigenous and scientific knowledge can provide significant ways of knowing and sensing the world that can build the resilience of social‐ecological systems. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Perceptions of Climate Change Abstract : Ways of knowing sea level rise: scientific measurement and modeling of global mean sea level rise (Figure: IPCC 2019) and local knowledge and experience of changes in the land‐sea interface (Plate: previous location of a relocated coastal village in Fiji, photo by Celia McMichael, 2015).